Innovative principles of the organization, use and protection of agricultural land - Butenko, E.; Stepanets, V. (Land Management, Cadastre and Land Monitoring, 2018)
The article considers innovative principles of development are explored. The role of land monitoring in the management of agricultural land use and the preconditions for improving agriculture has been highlighted. The concept of sustainable development of the use of land resources is proposed. The foreign experience and trends of sustainable land use development are described. Key words: land monitoring, innovative principles, land use, land protection.